2018
DOI: 10.2494/photopolymer.31.277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanoimprinting Multilayer Lift-off Process using Spin-on-glass for Nanogap Electrode Array

Abstract: Nanogap electrodes are expected to aid in the study of the electrical properties of single molecules and nanoparticles, and have also been applied to non-volatile memory. However, an electrode that exhibits a large area and good reproducibility is yet to be found. We investigate the nanogap fabrication method combining UV nanoimprint lithography and electromigration. A three-layer lift-off process, using spin-on-glass as an intermediate layer with high etching selectivity, is evaluated. Nanowire array patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Hashiguchi et al demonstrated the fabrication of platinum nanowires without burrs using a T-shaped structure of imprint resin/spin-on-glass/sacrificial layers. 25) However, the lift-off process through a T-shaped structure requires multiple coating and dry etching processes depending on the materials used in addition to the final wet development for removal of the sacrificial layer concomitantly with metal deposition. In a typical procedure, the ternary layers are made on a substrate surface by spin-coating and UV nanoimprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Hashiguchi et al demonstrated the fabrication of platinum nanowires without burrs using a T-shaped structure of imprint resin/spin-on-glass/sacrificial layers. 25) However, the lift-off process through a T-shaped structure requires multiple coating and dry etching processes depending on the materials used in addition to the final wet development for removal of the sacrificial layer concomitantly with metal deposition. In a typical procedure, the ternary layers are made on a substrate surface by spin-coating and UV nanoimprinting.…”
Section: Introductionmentioning
confidence: 99%